Long-term results of liver transplantation for hepatocellular carcinoma - M. Sh. Khubutia; Y. A. Kovalenko; A. O. Chugunov; A. V. Chzhao; K. R. Dzhagraev; A. A. Salienko; O. I. Andreytseva; L. V. Donova (Трансплантология (Москва))
In this article we presented the new approach to the liver transplantation based on the prognosis paradigm of the tumor recurrence before the operation using largest experience of the liver transplantation in Russia. The effect independent clinicopathologic factors on outcome were tested using univariate and multivariate analyses by the Cox regression. The value molecular biomarker for choice of the patients to the transplantation liver was presented.